2005
DOI: 10.1002/pi.1928
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam processing of nylon 6 and hydrogenated nitrile rubber (HNBR) blends: 1. Development of high strength heat‐ and oil‐resistant thermoplastic elastomers

Abstract: The effects of electron beam irradiation on the morphology, mechanical properties and heat and hot oil resistance of a thermoplastic elastomeric blend of 50/50 nylon 6 and HNBR rubber were investigated. The morphology of the blend was studied by scanning electron microscopy, with special reference to the effects of processing via injection moulding and the radiation dose. Irradiation of extruded pellets at low doses and subsequent injection moulding improved the blend morphology, thereby enhancing the mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…And in most cases, HNBR was used by blending with other elastomers such as FKM 5, 6. IR,7 NR,8 Nylon6,9, 10 and so on. At the same time some fillers like ZDMA,11 OMMT,12, 13 MWCNT,6, 14 were also incorporated to improve the properties, And yet HNBR filled with silica is few researched.…”
Section: Introductionmentioning
confidence: 99%
“…And in most cases, HNBR was used by blending with other elastomers such as FKM 5, 6. IR,7 NR,8 Nylon6,9, 10 and so on. At the same time some fillers like ZDMA,11 OMMT,12, 13 MWCNT,6, 14 were also incorporated to improve the properties, And yet HNBR filled with silica is few researched.…”
Section: Introductionmentioning
confidence: 99%
“…Electron‐beam processing and the changes in various technical properties of different polymer blends have also been investigated 21–25. The effect of the size of the dispersed NBR phase in poly(vinyl chloride) (PVC)/NBR blends on the stability of PVC to electron radiation has been studied by Li and Chan,26 where it was found that the compatibility increases when the average size of rubber‐rich domains is smaller.…”
Section: Introductionmentioning
confidence: 99%
“…The toughening of PAs via melt compounding with various rubbers (e.g., ethylene-propylene copolymer, ethylene-propylene-dieneterpolymer, styrene-ethylene/butadiene-styrene-with and without various functional groups for improved compatibility with PA) is recognized as a state-of-the-art procedure [10][11][12]. In fact, HNBR is the preferred component for temperature-and oil-resistant thermoplastic elastomers of the blend type, which often contain PAs [14,15]. In fact, HNBR is the preferred component for temperature-and oil-resistant thermoplastic elastomers of the blend type, which often contain PAs [14,15].…”
Section: Polymer Toughnessmentioning
confidence: 99%